Review of patterns in homicides by sharp force: one institution's experience - Handlos, Petr; Švecová, Tereza; Vrtková, Adéla; Handlosová, Klára; Dokoupil, Marek; Klabal, Ondřej; Timkovič, Juraj; Uvíra, Matěj (Forensic science, medicine, and pathology, 2023)
This paper presents a retrospective review of patterns found in cases of homicides by sharp force over a 13-year period at the Department of Forensic Pathology of the Ostrava University Hospital, Czech Republic. The review summarizes all frequently discussed aspects of such cases including the number and localization of injuries, the presence of defensive wounds, the type of the offending weapon, the cause of death, the place of death, victims' and perpetrators' profiles, their relationship, or toxicological findings. Furthermore, special attention was paid to the evaluation of any accompanying blunt force trauma that may be indicative of an escalation of the assault. The set of data was statistically analyzed. Even though most of the results of this review are consistent with available published studies, noteworthy differences have emerged in some aspects such as the sex and age of the victims, the relationship between the number of injuries suffered and the victims' sex, or the severity of alcohol intoxication in victims.
Keywords: Forensic Pathology; tupá poranění; Wounds, Nonpenetrating; lidé; retrospektivní studie; vražda; Crime Victims; Alcoholic Intoxication; oběti zločinu; Homicide; soudní patologie; Retrospective Studies; otrava alkoholem; Humans